Philosophy of science and meta-knowledge in international business and management - Devinney, Timothy M. 1956-; Pedersen, Torben; Tihanyi, Laszlo (College teacher) (Advances in international management ;, 2013)
This volume advances the debate on the past, present and future of international business and management research. A truly international group of experts present their perspectives, and ask the question What is it that we know? when discussing major issues and concepts in the field. This annual collection includes a regular special feature on a leading scholar; exploring in this volume the work of Jean-François Hennart and his theories on multinational enterprise and strategic management. Part two addresses international business and international management issues from a philosophical perspective, examining key topics such as post-merger integration, dominant design theory, internalizing firms and the strategy-performance relationship.